2018
DOI: 10.3389/fenrg.2018.00111
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment and Multi-Feed Anaerobic Co-digestion of Agro-Industrial Residual Biomass for Improved Biomethanation and Kinetic Analysis

Abstract: Batch biochemical methane potential (BMP) test of agro-industrial, agricultural, and municipal solid waste (MSW) individuals like groundnut straw, rice bran, and guar husk, mung bean husk (MBH), wheat straw (WS), and organic fraction of municipal solid waste (OFMSW), under mesophilic conditions, were performed to evaluate the biogas potential. BMP test for multi-feed anaerobic co-digestion (AcoD) of WS, OFMSW, and MBH at five mixing ratio was performed to evaluate the synergistic effect of multi feed-stocks of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 73 publications
(119 reference statements)
2
12
0
Order By: Relevance
“…4). The yield from treatment B and C is in agreement with what [29] reported in their experiment that groundnut shell pretreated with sonication released 469.36 ml biogas while the untreated substrate released 185.4 ml and [30,31] also reported that size reduction had positive effect on biogas yield. [32,33] reported that size reduction of pomace and maize fibre reduced to 0.4 mm particles size had faint effect on the gas produced and pace of their enzymatic hydrolysis.…”
Section: Effect Of Size Reduction On Organic Dry Matter Biogas Yieldsupporting
confidence: 90%
See 1 more Smart Citation
“…4). The yield from treatment B and C is in agreement with what [29] reported in their experiment that groundnut shell pretreated with sonication released 469.36 ml biogas while the untreated substrate released 185.4 ml and [30,31] also reported that size reduction had positive effect on biogas yield. [32,33] reported that size reduction of pomace and maize fibre reduced to 0.4 mm particles size had faint effect on the gas produced and pace of their enzymatic hydrolysis.…”
Section: Effect Of Size Reduction On Organic Dry Matter Biogas Yieldsupporting
confidence: 90%
“…This indicates that as the substrate tends to powdery form, the carbon/nitrogen ratio and organic dry matter were reducing. The methane percentage recorded for both treatments from this research are in the same range with what [26,29] recorded for treated groundnut shell and higher when compared with [5] 55 -75% methane and [35] who recorded 55 -65% methane. It shows that all the three sizes (2, 4 and 6 mm) produced good methane content and can be used when selecting substrate size for anaerobic digestion in terms of methane yield.…”
Section: Quality Of Biogas Producedsupporting
confidence: 79%
“…Over the past decade, anaerobic digestion (AD) has been used effectively for the degradation of agricultural lignocellulosic biomass-maize straw and wheat straw-for the production of biogas, which could be used for combined heat and power (CHP) application [12][13][14]. Paddy residues, composed of lignocellulose, are difficult for anaerobic microorganisms to degrade as they have a complex polymeric carbohydrates that must be preprocessed into simpler monomers-called platform molecules-that can be further converted into bioenergy [15].…”
Section: Anaerobic Digestion Of Lignocellulosic Biomassmentioning
confidence: 99%
“…Paddy residues, composed of lignocellulose, are difficult for anaerobic microorganisms to degrade as they have a complex polymeric carbohydrates that must be preprocessed into simpler monomers-called platform molecules-that can be further converted into bioenergy [15]. A number of researchers, however, have exclusively paid attention using rice straw for biogas generation through AD [14][15][16][17], but AD of pretreated paddy residues has rarely been reported.…”
Section: Anaerobic Digestion Of Lignocellulosic Biomassmentioning
confidence: 99%
See 1 more Smart Citation